Amanita fuliginea poisoning with thrombocytopenia: A case series. (30th January 2020) - Wang, Qiang; Sun, Meifeng; Lv, Hailin; Lu, Peng; Ma, Chengjun; Liu, Yun; Liu, Shuqin; Tong, Haiqing; Hu, Zhao; Gao, Yanxia
Abstract: Amanita fuliginea ( A. fuliginea ) poisoning is an uncommon and potentially fatal amatoxin exposure. We present 3 cases of severe A. fuliginea poisoning associated with thrombocytopenia in China. Three patients consumed foraged A. fuliginea and developed nausea, vomiting, abdominal pain, and diarrhea. They were transferred from primary clinics to our hospital 19–39 h after mushroom ingestion. They all presented with acute hepatic injury, coagulopathy, thrombocytopenia (6-41 × 10 9 /L), and positive fecal occult blood. Intravenous fluids and antioxidants were administered immediately after admission. Fibrinogen and platelets were given to patients A, B and C. Patient A developed fulminant liver failure and died on day 5 after mushroom exposure. Patients B and C recovered and were discharged on days 11 and 9, respectively. The main targets of A. fuliginea poisoning are the liver and digestive tract. To our knowledge this is the first report of thrombocytopenia associated with A. fuliginea ingestion. Highlights: Amanita fuliginea poisoning is uncommon and not well described in western literature. Thrombocytopenia associated with A. fuliginea ingestion was presented in the case series for the first time. Liver and digestive tract were main targets of A. fuliginea poisoning.